DIGITAL MARKETING TRANSFORMATION IN THE AI-FIRST ERA: A LITERATURE REVIEW ON INTERACTIVE VIDEO, SOCIAL COMMERCE, AND MULTI-SURFACE SEARCH OPTIMIZATION FOR INDONESIAN SMES - Indah Sulistiani; Syarifuddin; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study aims to examine digital marketing transformation in the AI-first era through a literature review focusing on interactive video, social commerce, and multi-surface search optimization for Indonesian small and medium-sized enterprises (SMEs). The rapid development of artificial intelligence, short-form video platforms, social commerce ecosystems, and AI-assisted search has changed how SMEs build visibility, engage consumers, and compete in digital markets. This study employs a qualitative library research method to analyze recent scholarly literature on AI-driven marketing, SME digital transformation, interactive video marketing, social commerce, search optimization, and digital competitiveness. The findings indicate that interactive video strengthens consumer engagement through visual storytelling, product demonstration, emotional connection, and real-time interaction. Social commerce enables SMEs to integrate promotion, communication, trust-building, and transaction within social media-based ecosystems. Meanwhile, multi-surface search optimization improves SME discoverability across search engines, marketplaces, social media, video platforms, map services, review platforms, and AI-generated search results. The study also shows that AI supports marketing efficiency through customer segmentation, content personalization, chatbot services, campaign automation, and data-driven decision-making. However, Indonesian SMEs still face challenges, including limited digital literacy, weak analytical capabilities, platform dependency, resource constraints, and inconsistent cross-platform branding. This review contributes to the literature by integrating interactive video, social commerce, and multi-surface search optimization into a conceptual framework for AI-first digital marketing to enhance SME competitiveness. The study recommends that Indonesian SMEs develop AI-enabled marketing capabilities, interactive content strategies, social commerce management, and multi-platform search visibility to strengthen sustainable and global competitiveness.